The revolutions trilogy - Banville, John (Picador, 2001)
"Doctor Copernicus tells of Nicholas Koppernigk, a scholar who determines, despite the conspiracies that rage round him and his ideas, to shatter the medieval view of the universe and find its 'secret music'." "Kepler is based on the life of one of the world's greatest astronomers and mathematicians, a man who found his drive to chart the geometry of the universe dependent on the whims of eccentric patrons and threatened by the politicized scholarship of his day." "The Newton Letter concerns a contemporary historian writing a biography of Isaac Newton. He retires to the country to finish his book, but is hampered when he becomes obsessed with Newton's nervous collapse in the summer of 1693, and with the family from whom he rents a summer cottage."--BOOK JACKET